Factors Associated with Mental Distress Among Medical Students of Universitas Pembangunan Nasional Veteran Jakarta - Anisya Zakiyyahaya Arvant; Sri Wahyuningsih; Suzy Yusna Dewi (Faculty of Medicine, Public Health, and Nursing, 2021)
Background: Mental distress refers to common mental disorders, such as depression, anxiety, and somatic symptoms, and is considered public health problem. It is reported that university students tend to have higher levels of mental distress compared to the general population, especially in medical students.Objective: The purpose of this study is to determine the risk factors affecting mental distress among medical students.Methods: A cross-sectional study using a survey was conducted among preclinical medical students at UPN Veteran Jakarta in June 2020. This study used proportional stratified sampling to complete questionnaires including demographic characteristics, adverse childhood experiences (ACE), family APGAR, and self-reporting questionnaire (SRQ-20). Data were analyzed by using logistic regression.Results: Among 138 participants, 36.2% had at least one of ACE, 55.1% of students came from a family with dysfunction, and 36.2% experienced mental distress. In multivariate analyses, some essential factors associated with mental distress are gender (OR=12.059, 95% CI: 2.311,62.916), adverse childhood experiences (OR=3.080, 95% CI: 1.903,4.983), family function (OR=2.733, 95% CI:1.097,6.809), and family structure (OR=0.290, 95% CI: 0.085,0.984).Conclusion: Students who are female, have history of adverse childhood experience, come from family with dysfunction, or non- nuclear family structure are more likely to be screened positive for mental distress. This study recommends an urgency of counselling service availability for medical students and community awareness to build a healthy family environment.